2015
DOI: 10.1007/s12041-015-0560-7
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone synthase genes from milk thistle (Silybum marianum): isolation and expression analysis

Abstract: Silymarin is a flavonoid compound derived from milk thistle (Silybum marianum) seeds which has several pharmacological applications. Chalcone synthase (CHS) is a key enzyme in the biosynthesis of flavonoids; thereby, the identification of CHS encoding genes in milk thistle plant can be of great importance. In the current research, fragments of CHS genes were amplified using degenerate primers based on the conserved parts of Asteraceae CHS genes, and then cloned and sequenced. Analysis of the resultant nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…The transcription level of CHS1 was significantly higher compared with CHS2 and CHS3 ( Figure 5). The obtained results were in agreement with previously reported studies [17,21]. Overall, our findings revealed that drought stress improved the expression of the three genes (CHS1, CHS2, and CHS3), which was coordinated by a definite increase in silymarin content (23.76 mg•g −1 DM) in milk thistle.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The transcription level of CHS1 was significantly higher compared with CHS2 and CHS3 ( Figure 5). The obtained results were in agreement with previously reported studies [17,21]. Overall, our findings revealed that drought stress improved the expression of the three genes (CHS1, CHS2, and CHS3), which was coordinated by a definite increase in silymarin content (23.76 mg•g −1 DM) in milk thistle.…”
Section: Discussionsupporting
confidence: 93%
“…Chalcone synthase (CHS) is a vital enzyme of the flavonoid and flavonolignans biosynthesis pathway [17,57]. Silymarin is synthesized in milk thistle plants via the phenylpropanoid pathway converting phenylalanine to 4-coumaroyl-CoA ( Figure S2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The direct precursors of the flavonolignans, the flavonoids and monolignols, are synthesized via the phenylpropanoid pathway transforming phenylalanine into 4-coumaroyl-CoA [2]. Cloning and characterization of a full-length chalcone synthase cDNA and one partial gene from S. marianum that is probably involved in flavonolignan biosynthesis have been reported recently [3]. …”
Section: Introductionmentioning
confidence: 99%